GEORGE EGERTON’S "VIRGIN SOIL": TWO CENTURIES IN ONE SHORT STORY - Figueirêdo, Suzan Martins (Caderno Seminal, 2017)
George Egerton, a pseudonym for Mary Chavelita Dunne, wrote the short story “Virgin Soil” in 1894 and, although within the text no information is given regarding the time when the story is supposed to have taken place, the very date of publication, put together with its attachment to the New Woman movement at the fin de siècle, marks it as a bridge between two centuries. In Egerton’s “Virgin Soil” both the structure, in two parts, and the two female characters, mother and daughter, represent conflicting models of womanhood at the fin de siècle. In those final decades of the nineteenth century, literature did not limit itself to portraying society as it was, but became actively involved in issues concerning women. Novels and short stories written by women of that time took a stance in the battle between forces demanding change and forces resisting innovation. This essay will look into how “Virgin Soil” illustrates both parties in the shape of the characters of mother and daughter themselves and in the literary choices she makes in the double structure of the text.